The Director : a novel - Ignatius, David, 1950- (2014)
After being told that his agency has been hacked, the director of the CIA launches a hunt into the hacker underground of Europe and America.
Keywords: United States. -- Central Intelligence Agency -- Fiction; Computer hackers -- Fiction; Computer crimes -- Fiction; Computer networks -- Security measures -- Fiction; Cyberterrorism -- Fiction; Suspense fiction; Spy stories